Fiber tract integrity in patients with brain injury and chronic health symptoms - Xiaojian Kang; John P. Coetzee; Keith L. Main; Srija Seenivasan; Kaitlly Zhu; Maheen M. Adamson (NeuroImage: Reports)
Patients with traumatic brain injuries (TBI), especially those with chronic health symptoms, often experience behavioral impairments attributable to white matter (WM) microstructural degeneration. Diffusion tensor imaging (DTI) is sensitive to these WM abnormalities, which are frequently a consequence of diffuse axonal injuries precipitated by the original trauma. In this study, tract profile analyses using an automated fiber quantification (AFQ) procedure compared diffusion properties along 20 major fiber tracts in a total of 46 participants, including individuals with TBI, who either have (n = 17) or did not have (n = 16) chronic symptoms, and a control group (n = 13). The tract profile analyses indicated that fractional anisotropy (FA) and radial diffusivity (RD) are more sensitive biomarkers of WM integrity than other commonly used diffusion measures, such as the linear anisotropy coefficient (CL) and mean diffusivity (MD). For all participants with TBI, FA was significantly lower and RD significantly higher in the middle portion of the left cingulum hippocampus (as compared to the control group). Additionally, FA was significantly lower in the inside segment of the left uncinate and the posterior segment of the inferior longitudinal fasciculus for TBI participants with chronic symptoms compared to the controls, but this was not the case for individuals with TBI without chronic symptoms. TBI participants with chronic symptoms also exhibited significantly lower fiber volume (VOL) in three other fiber tracts. This study provides evidence that the diffusion properties of discrete segments along the major fiber tracts, as measured by AFQ, can serve as biomarkers of WM abnormalities, especially for individuals with TBI and chronic health symptoms.